On the calibration of a shear stress criterion for rock joints to represent the full stress-strain profile - Akram Deiminiat; Jonathan D. Aubertin; Yannic Ethier (Journal of Rock Mechanics and Geotechnical Engineering, 2024)
Conventional numerical solutions developed to describe the geomechanical behavior of rock interfaces subjected to differential load emphasize peak and residual shear strengths. The detailed analysis of pre- and post-peak shear stress-displacement behavior is central to various time-dependent and dynamic rock mechanic problems such as rockbursts and structural instabilities in highly stressed conditions. The complete stress-displacement surface (CSDS) model was developed to describe analytically the pre- and post-peak behavior of rock interfaces under differential loads. Original formulations of the CSDS model required extensive curve-fitting iterations which limited its practical applicability and transparent integration into engineering tools. The present work proposes modifications to the CSDS model aimed at developing a comprehensive and modern calibration protocol to describe the complete shear stress-displacement behavior of rock interfaces under differential loads. The proposed update to the CSDS model incorporates the concept of mobilized shear strength to enhance the post-peak formulations. Barton's concepts of joint roughness coefficient (JRC) and joint compressive strength (JCS) are incorporated to facilitate empirical estimations for peak shear stress and normal closure relations. Triaxial/uniaxial compression test and direct shear test results are used to validate the updated model and exemplify the proposed calibration method. The results illustrate that the revised model successfully predicts the post-peak and complete axial stress–strain and shear stress–displacement curves for rock joints.